Movimento de borboletas frugívoras e conectividade funcional em uma paisagem de Mata Atlântica - Amaral, Priscila Lins Pimentel Figueiredo do (2012)
An organisms movement within and between habitats is an essential trait of life history, one that shapes population dynamics, communities and ecosystems in space and time. Since the ability to perceive and react to specific conditions varies greatly between organisms, different movement patterns are generated. These, in turn, will reflect the way species persist in the original habitat and surrounding patches. This study evaluated patterns of movement of frugivorous butterflies in order to estimate the connectivity of a landscape mosaic in an area of Atlantic Forest. For this purpose, we used the capture-mark-recapture method on butterflies trapped with fermented fruit bait in three distinct habitats. The first represents a typical Atlantic forest fragment, while the other two represent man-made matrix habitats. One contains a coconut plantation and the other a plantation of the exotic Acacia mangium species. Five traps were randomly placed in each landscape unit in areas of 40 x 40m. Using recapture data and relating it to distance between captures and habitat structure, I found that movement frequencies, both within and between landscape units were different for the analyzed species, suggesting that they do not interpret and react to the landscape in the same way. Thus this study was able to measure landscape functional connectivity. For most species, the exchange between forest and coconut plantations occurred with low frequency compared to exchanges between the forest and acacia plantations, which share more structural similarities. This seems to indicate that a matrix that is more similar to patches of native vegetation can shelter species, permit their movement and, consequently, contribute to the landscape connectivity